2020
DOI: 10.21203/rs.3.rs-22941/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality of antenatal care experience in rural Bangladesh: social support, respect, dignity, communication and counselling

Abstract: Background Quality antenatal care (ANC) can contribute to reducing maternal and neonatal morbidity and mortality. Very little information is available on the experience of care during ANC contacts in Bangladesh. This study aims to understand social support received by women, their experience of respect and dignity, and quality of communication and counselling during ANC contacts in rural Bangladesh for improving the quality of ANC services. Methods A cross-sectional household survey was administered in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…One of the possible ways we can ensure birth preparedness is by providing quality antenatal care. However, there are gaps in provision of quality ANC with appropriate counselling in Bangladesh [ 30 ]. A national community survey reported only 18% of women received quality ANC and only 40% of mothers who received ANC reported that providers informed them of the signs of possible pregnancy complications during the visit [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible ways we can ensure birth preparedness is by providing quality antenatal care. However, there are gaps in provision of quality ANC with appropriate counselling in Bangladesh [ 30 ]. A national community survey reported only 18% of women received quality ANC and only 40% of mothers who received ANC reported that providers informed them of the signs of possible pregnancy complications during the visit [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the involvement of husbands and/or closest family members can help health workers to provide comprehensive health information. Therefore, it is imperative to conduct trainings for every health worker that aim to improve their interpersonal and communication skills so that in its implementation health workers can provide care according to the capacity and topics discussed (Mhajabin et al, 2020).…”
Section: B Doctor: Interpersonal Communication Practicementioning
confidence: 99%
“…Hal ini bertujuan untuk meningkatkan kemampuan dan menggali potensi diri serta kecakapan yang dimiliki, sehingga dapat melakukan suatu pekerjaan dalam bidang tertentu (Ravanfar, 2018). Penelitian lain menyebutkan pelatihan setiap tenaga kesehatan secara signifikan meningkatkan keterampilan interpersonal dan komunikasi, sehingga dalam pengimplementasiannya tenaga kesehatan dapat memberikan asuhan sesuai kapasitas dan topik yang didiskusikan (Mhajabin et al, 2020).…”
Section: Pembahasanunclassified